Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Normalization of candidate reference genes for precise qRT-PCR quantification in Maruca vitrata F. (Lepidoptera: Crambidae) under multiple biotic and abiotic stress regimes - C. R. Chandana; Sushila Nadagouda; Muthugounder Mohan; A. Sunny Rao; Basavaraj S. Kalmath; Shivaleela Gouda; Jayaprakash M. Nidagundi; Saroja Narsinga Rao (International Journal of Tropical Insect Science, 2026)

Spatial distribution of metals in soils of an ecologically sensitive forest region of the Western Ghats, South India: vertical profiles, enrichment status, and health risk assessment - A. Sudha; C. S. Ratheesh Kumar; Roshni Mohan; P. V. Vidya; U. Sreejisha (Environmental Monitoring and Assessment, 2026)

Characterization and source attribution of PM2.5 in a coal mining town in India: Insights from residential and roadside microenvironments - Kamlika Gupta; Victor Wei-Chung Chang; Mohan Yellishetty; Harish C. Phuleria (Environmental Research, 2026)

Integrated enzyme-assisted hot water biorefinery for enhanced recovery of bioactive compounds from brown seaweeds - C. S. Tejpal; S. M. Vijayakumar; K. M. Pradeep; Rahman K. Habbeb; T. G. Sumithra; C. O. Mohan; T. K. Anupama; R. Anandan (Journal of Applied Phycology, 2026)

Sedimentary phosphorous fraction composition in Ashtamudi wetland: implications on nutrient mobility, bioavailability, trophic state, and pollution - Roshni Mohan; Ratheesh Kumar C. S.; Sudha A.; Sreejisha U (Environmental Monitoring and Assessment, 2026)

Influence of larval diet on the life table traits of Chrysoperla zastrowi sillemi using age-stage two-sex life table: insights for mass production - K. T. Shivakumara; T. Venkatesan; S. S. Udikeri; M. C. Keerthi; T. Sudha; M. Mohan; C. Manjunatha; G. S. Guruprasad (Journal of Plant Diseases and Protection, 2026)

Comprehensive assessment of PM2.5 exposures around a regional mining site in India: integrating chemical composition, oxidative potential and health risk - Kamlika Gupta; Victor Wei-Chung Chang; Mohan Yellishetty; Harish C. Phuleria (Environmental Geochemistry and Health, 2026)

Plant isopropylmalate synthases: in and beyond leucine biosynthesis - Mohan Varghese; Asif Lone; Naveen C. Bisht (Planta, 2026)

Derivation of seawater quality criteria for copper, cadmium, zinc, and mercury for the coastal and coral reef ecosystems of Gulf of Mannar, India - C M Ramakritinan; M Anand; L Palanikumar; Manoj Singh; S Manikandan; G Jayanthi; A K Kumaraguru; D Mohan; T Balasubramanian; B R Subramanian (Journal of Earth System Science, 2026)

A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Characterization, genomic insights and anti-biofilm potential of phage vB_PaeM_PKMS3, a lytic Pbunavirus capable of infecting clinical Pseudomonas aeruginosa isolates - Nivedya Mohan; K. S. Sritha; Jiya Jose; Sumi J. Menachery; Chandini C. Mohan; Asna T. Isshack; Honey Gopinathan; Sayuj Koyyappurath; K. Abhitha; Yogesh Bharat Dalvi; Sarita G. Bhat (Antonie van Leeuwenhoek, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Radiant solutions: Unlocking the mysteries of Mn2+ and Pd2+ with a mobile fluorescence wizard - Virender; Manpreet Kaur; Hari Om; Bakhtiyar Najafov; Ashok Kumar Sharma; Ismayil M. Garazade; M.Fátima C. Guedes da Silva; Armando J.L. Pombeiro; Wei Sun; Brij Mohan (Journal of Hazardous Materials, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Date Palm (Phoenix dactylifera L.) Microsatellites: Genome-Wide Resource for Diversity Analysis and Cross-Transferability in Arecaceae - Darshan T. Dharajiya; Bhemji P. Galvadiya; Piyush Verma; Anuj Kumar Singh; Kapil Mohan Sharma; D. A. Baidiyavadra; C. M. Muralidharan; Kapil K. Tiwari (Sugar Tech, 2025)

Assessment of Genetic Variability of Date Palm (Phoenix dactylifera L.) Grown Under Arid Ecosystem of Gujarat, India - Kapil Mohan Sharma; Piyush Verma; Nishit V. Soni; Kapil K. Tiwari; D. A. Baidiyavadra; Mani N. Chaudhari; Bhargav B. Golakiya; P. C. Joshi (Sugar Tech, 2025)

Physicochemical and Antioxidant Characterization of Blended Spice-Flavoured Jaggery Cubes During Storage - Meera Mohan; E. Jayashree; P. V. Alfiya; K. Anees; C. Sarathambal (Sugar Tech, 2025)

Pharmacognostical studies of the leaf and stem of Tetrastigma leucostaphylum (Dennst.) Alston ex Mabb. with special reference to soil chemistry - Stephy P. P.; Prasobh K. Mohan; Adarsh Krishna T.P.; Ajeesh Krishna T.P.; Selva Kumar S.; Walter Christhuraj C.; Soosai Raj S. (Vegetos, 2025)

Plastic Biofilms as Hotspots of Nitrogen Cycling in Estuarine Ecosystems: Comparative Ecological, Genomic, and Transcriptomic Analysis Across Substrates - Xinrong Huang; Leyang Yang; Shuyidan Zhou; Lei Zhong; Guanghui Xu; Mohan Bi; Xiaoru Yang; Xiaoxuan Su; Matthias C. Rillig (Global Change Biology, 2025)
Biofilms represent a ubiquitous microbial lifestyle that facilitates colonization, symbiosis, and nutrient cycling, shaping environmental chemical transformations. In the Anthropocene, the proliferation of artificial surfaces, particularly plastics, has introduced novel and artificial ecological niches for microbial colonization. However, the biogeochemical potential of biofilms on these emerging artificial substrates remains largely unknown. Here, using 15 N tracing, amplicon, metagenome, and metatranscriptomic sequencing, we explore nitrogen (N) potential biogeochemistry across artificial and natural biofilms as well as the bulk seawater. Our results reveal that plastic biofilms exhibit enhanced N transformation potential, including elevated nitrification (2~45‐fold), denitrification (5~44‐fold), and N 2 O production (3~13‐fold) rates, compared to natural biofilms and ambient seawater. This functional shift corresponds to distinct microbial community structures, driven by active N‐cycling taxa and metabolic pathway reconfigurations on plastic surfaces. We also observe that carbohydrate metabolism pathways, such as glycolysis and the pentose phosphate pathway, were highly expressed in plastic biofilms, with transcriptional levels of glk (encoding glucokinase) and PGK (encoding phosphoglycerate kinase) increased by 6‐ and 2‐fold, respectively. Our findings depict the role of plastic biofilms as active participants in estuarine N cycling and underscore the broader implications of plastic pollution on ecosystem biogeochemistry.

Prospecting indigenous Bt isolates for bioinsecticidal efficiency against soil-borne white grub, Holotrichia serrata (F.) (Coleoptera: Scarabaeidae) - M. Manoj; K. Tamilvendan; Mohan Chavan; G. Selvakumar; K. Nagaraju; C. Manjunatha (Journal of Asia-Pacific Entomology, 2025)

Soil properties explain the variability in tire wear particle effects in soil based on a laboratory test with 59 soils - Tingting Zhao; Yaqi Xu; Mohan Bi; Huiying Li; Guanlin Li; Matthias C. Rillig (Environmental Pollution, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Assessment of sweetpotato germplasm for selection of day-neutral genotypes for tropical India - Shirly Raichal Anil; M. N. Sheela; C. Mohan; A. N. Jyothi; C. Visalakshi Chandra; S. Shanawas; J. Sreekumar (Euphytica, 2025)

Shared autoimmune pathways: A transcriptomic analysis of type 1 diabetes and celiac disease - Prasanna Kumar Selvam; Santhosh Mudipalli Elavarasu; T Dhanushkumar; Supraja Mohan; George Priya Doss C; Karthick Vasudevan (Next Research, 2025)

Biogenic synthesis of metal oxide nanoparticles for the elicitation of secondary metabolites in the in vitro propagated plantlets of Rubia cordifolia L. - Aparna Prasad; Jameema Sidhic; C. K. Sruthi Mohan; Paromita Sarbadhikary; Satheesh George; Arunaksharan Narayanankutty; Renjis T. Tom; Blassan P. George; Heidi Abrahamse (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
In recent decades, nanoparticles (NPs) have become an important focus of research with diverse applications in industries such as food, cosmetics, and medicine. Recent studies have demonstrated that nanomaterials can boost the production of secondary metabolites in plants. In vitro techniques coupled with nanotechnology tools provide an attractive alternative for enhancing the production of targeted dye products (Alizarin and Purpurin) from crops. In this study, biocompatible hexagonal-shaped Zinc oxide nanoparticles and monoclinic-spherical-shaped Copper oxide nanoparticles (CuO NPs) were synthesized from the stem extract of Rubia cordifolia L., with average particle sizes of 17.9 nm and 28.35 nm, respectively. Quantitative phytochemical assessments, HRLC-MS analysis, HPTLC fingerprinting, and antioxidant properties in methanolic extracts of in vitro treated plants with different concentrations of metallic oxide NPs showed variations, in both quality and quantity of secondary metabolites. The treatment of 0.1 mg/L CuO NPs showed the highest level of secondary metabolites including alizarin and purpurin. Notably, concentrations exceeding 10 mg/L transformed these nanoparticles from elicitors to potentially toxic components for the plantlets. The extracts elicited by CuO NPs (0.1 mg/L) exhibited high antioxidant activity due to these metabolic changes. CuO NP treatment provided a useful and efficient in vitro technique to enhance the synthesis of plant based bioactive compounds with potential applications in the pharmaceutical and textile industry.

Efficacy of Duddingtonia flagrans spores fed in trace mineral mix to lambs in reducing the development of gastrointestinal nematode larvae in feces - Joan M. Burke; Suman Rohila; Elisa Preston; Cathleen C. Williams; Clare M. Scully; Brooke A. Delcambre; Katherine H. Petersson; Elizabeth Kass; Mohan Acharya; James E. Miller; Adriano F. Vatta (Veterinary Parasitology, 2025)

Evaluating the reinforcing potential of steam-exploded chitin nanocrystals in chitosan-based biodegradable nanocomposite films for food packaging applications - Soibam Ngasotter; K.A. Martin Xavier; C. Sagarnaik; Remya Sasikala; C.O. Mohan; Bindu Jaganath; George Ninan (Carbohydrate Polymers, 2025)

Discovering the role of fairy ring fungi in accelerating nitrogen cycling to promote plant productivity in grasslands - Mohan Liu; Yuqi Wei; Lu Lian; Junling Zhang; Nan Liu; Gail W.T. Wilson; Matthias C. Rillig; Shangang Jia; Gaowen Yang; Yingjun Zhang (Soil Biology and Biochemistry, 2024)

Chromoionophores decorated silica-polymer hybrid monolith as the solid-state optical sensor for the simultaneous detection of Pb2+, Hg2+, and Cd2+ in aqueous and cigarette samples - Sangeetha Krishna Kumar; Prabhakaran Deivasigamani; Satheesh Kuppusamy; Pitchaiah K Chinaraga; C V S Brahmmananda Rao; Sivaraman Nagarajan; Akhila Maheswari Mohan (Journal of Environmental Chemical Engineering, 2024)

Utilization of water chestnut waste for biohydrogen production and enhanced power generation by stacked microbial fuel cell - Soumyajit Chandra; Soumya Pandit; Soma Deb; C. Mohan; Mithul Rajeev; Nishant Ranjan; Ashish Kumar; Pritam Kumar Dikshit (Biocatalysis and Agricultural Biotechnology, 2024)

Effect of Storage Temperature and Containers on Date Palm (Phoenix dactylifera L.) Pollen Viability and Post-storage Pollination - Kapil Mohan Sharma; Devshi A. Baidiayavadra; C. M. Muralidharan; C. N. Panchal; Piyush Verma (Sugar Tech, 2024)

Physiological Responses to Acute Heat Stress in Rohu, Labeo rohita: Insights from Liver Proteomics - Mohan R. Badhe; Priyanka Das; Sonalina Sahoo; Anirban Paul; Pramoda Kumar Sahoo; R. Rajendra Kumar Reddy; Amol R. Suryawanshi; Priyanka C. Nandanpawar; Kanta Das Mahapatra; Naresh S. Nagpure; Mukunda Goswami; Jyotirmaya Mohanty (Marine Biotechnology, 2024)

In silico analysis and designing gRNA constructs for the precise modification of the OsTMS5 gene in rice (Oryza sativa L.): a comprehensive study and construct development for crop improvement - Laxmipreeya Behera; Kailash Ch. Samal; C. Parmeswaran; Pawan Kumar Agrawal; V. Mohan Murali Achary; Manasi Dash; Sanat Kumar Dwibedi; Raj Kumari Bhol; Bhagwat Singh Kherawat; Sang-Min Chung; Manzer H. Siddiqui; Saud Alamri; et al. (Cereal Research Communications, 2024)

Dysesthesias and migratory myalgias: clinical clues to suspect neuroangiostrongyliasis - Kavadisseril Vivekanandan Vysakha; Anil Kumar; Sitara Swarna Rao Ajjampur; Sarath Mohan; C. P. Reshmi; Aravind Reghukumar (Acta Neurologica Belgica, 2024)

Carbothermally synthesized, lignin biochar-based, embedded and surface deposited nano zero-valent iron composites: Comparative material characterization, selective gas adsorption and nitroaromatics remediation - Yasmitha A. Alahakoon; Shine C. Wilson; Chathuri Peiris; Yohara K. Ranasinghe; Sameera R. Gunatilake; Xuefeng Zhang; Todd E. Mlsna; Upul Kumarasinghe; M.Infas H Mohideen; Upendar Reddy Gandra; Anish Mathai Varghese; Georgios N. Karanikolos; et al. (Colloids and Surfaces C: Environmental Aspects, 2024)

Macroscale properties and atomic-scale mechanisms of ash removal in low-temperature hydrothermal carbonization - Yan Yu; Zhangmin Wan; Micholas Dean Smith; Mood Mohan; Shahabaddine Sokhansanj; Anthony Lau; Jeremy C. Smith; Orlando J. Rojas (Chemical Engineering Journal, 2024)

Performance evaluation of bio-concrete: An analysis of biomineralization capabilities, microstructural and mechanical properties - Priya S. Nair; Rajesh Gupta; Vinay Agrawal; Niha Mohan K; Blessen Skariah Thomas; Shanone C. Pereira; Abhishek Jain (Sustainable Chemistry and Pharmacy, 2024)

Chromoionophoric molecular probe infused bimodal porous polymer rostrum as solid-state ocular sensor for the selective and expeditious optical sensing of ultra-trace toxic mercury ions - Prabhakaran Srinivasan; Sushmitha P Sivaraman; Akhila Maheswari Mohan; Deepan Kumar Madhu; Pitchaiah K Chinaraga; C V S Brahmananda Rao; Sivaraman Nagarajan; Prabhakaran Deivasigamani (Journal of Hazardous Materials, 2024)

Synergistic effect in ZIF-67/MoS2 entrenched MWCNT photo (electro) catalyst for degradation of tetracycline and alternative to Pt counter electrode in dye-sensitized solar cells - K. Aravinthkumar; Bhanupriya Das; Shiao-Shing Chen; C. Raja Mohan (Journal of Environmental Chemical Engineering, 2024)

Shake-table testing of two adjacent similar building frames connected with optimal viscoelastic dampers - Ramakrishna Uppari; S. C. Mohan (Innovative Infrastructure Solutions, 2024)

Probing the origins of programmed death ligand-1 inhibition by implementing machine learning-assisted sequential virtual screening techniques - Shruthy Kuttappan; Ratul Bhowmik; C. Gopi Mohan (Molecular Diversity, 2024)

Soil Carbon Sequestration and Agronomic Productivity as Influenced by the Long-Term Organic and Inorganic Fertilisation Under the Upland Rice–Wheat System in Vertisols of Central India - Ch. Srinivasarao; Sumanta Kundu; D. P. Dubey; Rajiv Dubey; S. Rakesh; Rattan Lal; P. C. Abhilash; J. V. N. S. Prasad; G. Pratibha; Somasundaram Jayaraman; K. Mrunalini; K. A. Gopinath; et al. (Anthropocene Science, 2024)

Short-term time-series observations of phytoplankton light-absorption and productivity in Prydz Bay, coastal Antarctica - Sarat C. Tripathy; Anvita U. Kerkar; P. Sabu; Sunil K. Padhi; Sudarsana R. Pandi; Amit Sarkar; Bhaskar V. Parli; Rahul Mohan (Frontiers in Marine Science, 2024)
The optical characteristics of coastal Antarctic waters exhibit complexity due to the dynamic hydrography influenced by meltwater intrusion, which alters nutrient levels, thermohaline structure, and optically active substances (OAS) regimes. Studies on bio-optical variability and its implications on phytoplankton productivity (PP) are scanty in coastal polar regions. On this backdrop, time-series measurements (72 h at 6 h intervals) of bio-optical properties such as phytoplankton biomass (chlorophyll-a), absorption (a ph ), and total suspended matter (TSM) concurrently with PP were measured to understand their interplay and variability in relation to the ambient physicochemical settings in the under-sampled Prydz Bay, coastal Antarctica. Our findings revealed thermohaline stratification within the bay, likely attributed to the inflow of less saline meltwater from nearby glaciers and minimal wind activity. The consistent presence of sub-surface chlorophyll maximum (SCM) beneath the stratified layer underscored the light-acclimatization response of shade-adapted phytoplankton. Surface waters exhibited higher TSM compared to deeper layers, indicating glacial melt influence, while the depth of the sunlit layer remained relatively stable, suggesting limited water mass movement and/or variability in OAS at the study site. An inverse relation between chlorophyll-a and chlorophyll-a-specific phytoplankton light absorption (a* ph (λ)) manifested ‘pigment package effect’ within the prevailing phytoplankton community, implying reduced light-absorption efficiency and consequent lower PP. Compared to chlorophyll-a, the phytoplankton light absorption (a ph (λ)) emerged as a better proxy for explaining PP variability. Nutrient availability was not limiting, which was conducive to micro (large) phytoplankton growth. Classification of phytoplankton size classes (micro, nano, and pico) based on the B/R ratio (a ph at Blue (443 nm)/Red (676 nm) region) confirmed the dominance of larger (micro) phytoplankton that are more susceptible to package effect, thus have implications on reduced PP potential of this polar marine ecosystem.

Evaluation of WRF Cloud Microphysics Schemes in Explicit Simulations of Tropical Cyclone ‘Fani’ Using Wind Profiler Radar and Multi-Satellite Data Products - P. Reshmi Mohan; C. Venkata Srinivas; V. Yesubabu; T. Narayana Rao; B. Venkatraman (Pure and Applied Geophysics, 2024)
Extremely severe cyclonic storm (ESCS) ‘Fani’ formed in the North Indian Ocean and crossed at Puri in Orissa State on the east coast of India on 03 May 2019. In this study, we examine the sensitivity of convection permitting WRF simulations (3 km) of ‘Fani’ to cloud microphysics (CMP) schemes using radar and multi-satellite data products. Five CMP schemes, namely Thompson, Goddard, WSM6, Morrison and Lin are tested in WRF. Results show that the changes in the CMP schemes primarily affect the simulated intensity and have lesser impact on the track predictions. Simulations with Thompson followed by Goddard produced the best predictions for both track and intensity estimates. Our analysis reveals significant variations in vertical motions associated with Fani across different CMP schemes; the WSM6, Goddard and Lin schemes produced relatively stronger vertical motions. The explicit WRF simulations could reproduce the wind profiler radar observed intense convective motions during the transit of Fani between 1 and 2 May 2019 at Gadanki station. Experiments with Thompson and Goddard schemes simulated the mean vertical velocities in lower, middle and upper layers in better agreement with radar data. The Lin, WSM6 and Goddard CMP predicted stronger updraft velocities (~ 0.35 m/s); Thompson produced moderate updraft velocities (~ 0.25 m/s) in the upper troposphere over a relatively wider area of high theta-e (385–390 K) indicating the simulation of a convectively stronger and warmer core compared to Morrison. Our analysis suggests that the differences in vertical motions in various CMP simulations are mainly due to the variations in the warming in simulations. It has been found that WSM6, Lin and Goddard produced a deeper core (up to 200 hPa) with a stronger diabatic heating of ~ 6° C followed by Thompson, which simulated a moderately deep core extending to ~ 250 hPa with moderate heating of ~ 5 °C whereas Morrison produced a relatively weak core with a heating of ~ 4 °C limited to 300 hPa. The stronger simulated diabatic heating in Lin, WSM6 and Goddard produces stronger inflow, moisture convergence in the lower levels and stronger outflow and divergence in the upper levels leading to stronger convection in the core region in these cases. The Lin, WSM6 and Goddard mixed phase schemes with more solid hydrometeors simulated stronger radar reflectivities, and stronger eyewalls, due to more latent heat release leading to the development of a strong warm core in the upper troposphere and thus a stronger TC.

Genetic diversity studies between Ipomoea wild species and cultivated sweet potato (Ipomoea batatas (L.) Lam.) using SSR markers - M.S. Amritha; O.G. Dhanya; Aswathy G.H. Nair; P. Vidya; Senthilkumar K. Muthusamy; C. Mohan (South African Journal of Botany, 2024)

Elucidation of novel drought-responsive genes from tuber transcriptome of cassava under water deficit stress - A.V.V. Koundinya; Senthilkumar K. Muthusamy; B.R. Ajeesh; C. Mohan; J. Sreekumar; Sowmya Pulapet; Kesavan Markkandan; M.N. Sheela (South African Journal of Botany, 2024)

Electron transfer enhanced catalytic activity of nitrogen doped reduced graphene oxide supported CuCo2O4 towards the fast reduction of 4-nitrophenol in water - Bibin Jacob; Manoj Mohan; Dhanyaprabha K C; Hysen Thomas (Environmental Research, 2024)

Oschib1 gene encoding a GH18 chitinase confers resistance against sheath blight disease of rice caused by Rhizoctonia solani AG1-IA - Naresh Babu Prathi; Chagamreddy Venkata Durga Rani; Vellaisamy Prakasam; Yeshala Chandra Mohan; Gandikota Mahendranath; G. K. Sri Vidya; C. N. Neeraja; Raman Meenakshi Sundaram; Satendra K. Mangrauthia (Plant Molecular Biology, 2024)

Structurally engineered probe infused porous polymer monolith as a solid-state visual sensing platform for Cd2+ ions - Sangeetha Krishna Kumar; Satheesh Kuppusamy; Anju Pavoor Veedu; Pitchaiah Kancharlapalli Chinaraga; C V S Brahmmananda Rao; Sivaraman Nagarajan; Prabhakaran Deivasigamani; Akhila Maheswari Mohan (Journal of Environmental Chemical Engineering, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Geochemical partitioning of sediment-bound phosphorous in Thrissur Kole Wetlands, Southwest India: Status of bioavailability and trophic state - P. V. Vidya; S. Rajathy; C. S. Ratheesh Kumar; S. K. Maneesh Kumar; K. B. Akhilesh; R. Mohan; A. Sudha (International Journal of Environmental Science and Technology, 2024)

How widespread use of generative AI for images and video can affect the environment and the science of ecology - Matthias C. Rillig; India Mansour; Stefan Hempel; Mohan Bi; Birgitta König‐Ries; Atoosa Kasirzadeh (Ecology Letters, 2024)
Generative artificial intelligence (AI) models will have broad impacts on society including the scientific enterprise; ecology and environmental science will be no exception. Here, we discuss the potential opportunities and risks of advanced generative AI for visual material (images and video) for the science of ecology and the environment itself. There are clearly opportunities for positive impacts, related to improved communication, for example; we also see possibilities for ecological research to benefit from generative AI (e.g., image gap filling, biodiversity surveys, and improved citizen science). However, there are also risks, threatening to undermine the credibility of our science, mostly related to actions of bad actors, for example in terms of spreading fake information or committing fraud. Risks need to be mitigated at the level of government regulatory measures, but we also highlight what can be done right now, including discussing issues with the next generation of ecologists and transforming towards radically open science workflows.

A new machine learning approach for estimating shear wave velocity profile using borelog data - Anushka Joshi; Balasubramanian Raman; C. Krishna Mohan; Linga Reddy Cenkeramaddi (Soil Dynamics and Earthquake Engineering, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Combined application of up to ten pesticides decreases key soil processes - Peter Meidl; Anika Lehmann; Mohan Bi; Carla Breitenreiter; Jasmina Benkrama; Erqin Li; Judith Riedo; Matthias C. Rillig (Environmental Science and Pollution Research, 2024)
Natural systems are under increasing pressure by a range of anthropogenic global change factors. Pesticides represent a nearly ubiquitously occurring global change factor and have the potential to affect soil functions. Currently the use of synthetic pesticides is at an all-time high with over 400 active ingredients being utilized in the EU alone, with dozens of these pesticides occurring concurrently in soil. However, we presently do not understand the impacts of the potential interaction of multiple pesticides when applied simultaneously. Using soil collected from a local grassland, we utilize soil microcosms to examine the role of both rate of change and number of a selection of ten currently used pesticides on soil processes, including litter decomposition, water stable aggregates, aggregate size, soil pH, and EC. Additionally, we used null models to enrich our analyses to examine potential patterns caused by interactions between pesticide treatments. We find that both gradual and abrupt pesticide application have negative consequences for soil processes. Notably, pesticide number plays a significant role in affecting soil health. Null models also reveal potential synergistic behavior between pesticides which can further their consequences on soil processes. Our research highlights the complex impacts of pesticides, and the need for environmental policy to address the threats posed by pesticides.

Biomass pretreatment with distillable ionic liquids for an effective recycling and recovery approach - Ezinne C. Achinivu; Brian W. Blankenship; Nawa Raj Baral; Hemant Choudhary; Ramu Kakumanu; Mood Mohan; Edward E.K. Baidoo; Corinne D. Scown; Anthe George; Blake A. Simmons; John Gladden (Chemical Engineering Journal, 2024)

Application of a new machine learning model to improve earthquake ground motion predictions - Anushka Joshi; Balasubramanian Raman; C. Krishna Mohan; Linga Reddy Cenkeramaddi (Natural Hazards, 2024)

Application of XGBoost model for early prediction of earthquake magnitude from waveform data - Anushka Joshi; Chalavadi Vishnu; C Krishna Mohan; Balasubramanian Raman (Journal of Earth System Science, 2023)

Development of low-cost base isolation technique using multi-criteria optimization and its application to masonry building - Zoheb Nawaz Md; Mohan S C; Sri Kalyana Rama Jyosyula (Soil Dynamics and Earthquake Engineering, 2023)

From the basics to emerging diagnostic technologies: What is on the horizon for tilapia disease diagnostics? - Ha Thanh Dong; Thawatchai Chaijarasphong; Andrew C. Barnes; Jérôme Delamare‐Deboutteville; Peiyu Alison Lee; Saengchan Senapin; Chadag Vishnumurthy Mohan; Kathy F. J. Tang; Sharon E. McGladdery; Melba G. Bondad‐Reantaso (Reviews in Aquaculture, 2023)
Tilapia is an affordable protein source farmed in over 140 countries with the majority of production in low‐ and middle‐income countries. Intensification of tilapia farming has exacerbated losses caused by emerging and re‐emerging infectious diseases. Disease diagnostics play a crucial role in biosecurity and health management to mitigate disease loss and improve animal welfare in aquaculture. Three continuous levels of diagnostics (I, II and III) for aquatic species have been proposed by Food and Agriculture Organization of the United Nations (FAO) and the Network of Aquaculture Centers in Asia and the Pacific (NACA) to promote the integration of basic and advanced methods to achieve accurate and meaningful interpretation of diagnostic results. However, the recent proliferation of cutting‐edge molecular methods applied in the diagnosis of diseases of aquacultured animals has shifted the focus of researchers and users away from basic approaches and toward molecular diagnostics, despite the fact that many diseases can be rapidly diagnosed using inexpensive, simple microscopic examination and that most emerging diseases in aquaculture were discovered by histopathology. This review, therefore, revisits and highlights the importance of the three levels of diagnostics for diseases of tilapia, particularly the frequently overlooked basic procedures (e.g., case history records, gross pathology, presumptive diagnostic methods and histopathology). The review also covers current and emerging molecular diagnostic technologies for tilapia pathogens including polymerase chain reaction methods (conventional, quantitative, digital), isothermal amplification methods Loop‐mediated Isothermal Amplification (LAMP), recombinase polymerase amplification (RPA), clustered regularly interspaced short palindromic repeats (CRISPR)‐based detection, lateral flow immunoassays, as well as discussing what is on the horizon for tilapia disease diagnostics (next generation sequencing, artificial intelligence, environmental Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA) and point‐of‐care testing) providing a future vision for transferring these technologies to farmers and stakeholders for a sustainable aquatic food system transformation.

Gut–Brain Axis, Neurodegeneration and Mental Health: A Personalized Medicine Perspective - Alisha Chunduri; S. Deepak Mohan Reddy; M. Jahanavi; C. Nagendranatha Reddy (Indian Journal of Microbiology, 2022)

Nutritional Crispy from Fish Scales for Human Diet - K. R. Sreelakshmi; Rehana Raj; S. Remya; V. A. Minimol; C. O. Mohan; George Ninan (Journal of Aquatic Food Product Technology, 2022)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Machine learning models for predicting the activity of AChE and BACE1 dual inhibitors for the treatment of Alzheimer’s disease - G. Dhamodharan; C. Gopi Mohan (Molecular Diversity, 2022)

Crystal structure and metal binding properties of the periplasmic iron component EfeM from Pseudomonas syringae EfeUOB/M iron-transport system - Mohan B. Rajasekaran; Rohanah Hussain; Giuliano Siligardi; Simon C. Andrews; Kimberly A. Watson (BioMetals, 2022)
EfeUOB/M has been characterised in Pseudomonas syringae pathovar. syringae as a novel type of ferrous-iron transporter, consisting of an inner-membrane protein (EfeU Psy ) and three periplasmic proteins (EfeO Psy , EfeM Psy and EfeB Psy ). The role of an iron permease and peroxidase function has been identified for the EfeU and EfeB proteins, respectively, but the role of EfeO/M remains unclear. EfeM Psy is an ‘M75-only’ EfeO-like protein with a C-terminal peptidase-M75 domain (EfeO II /EfeM family). Herein, we report the 1.6 Å resolution crystal structure of EfeM Psy , the first structural report for an EfeM component of P. syringae pv . syringae . The structure possesses the bi-lobate architecture found in other bacterial periplasmic substrate/solute binding proteins. Metal binding studies, using SRCD and ICP-OES, reveal a preference of EfeM Psy for copper, iron and zinc. This work provides detailed knowledge of the structural scaffold, the metal site geometry, and the divalent metal binding potential of EfeM. This work provides crucial underpinning for a more detailed understanding of the role of EfeM/EfeO proteins and the peptidase-M75 domains in EfeUOB/M iron uptake systems in bacteria.

Convection-Permitting WRF Simulations of Tropical Cyclones Over the North Indian Ocean - P. Reshmi Mohan; C. Venkata Srinivas; B. Venkatraman (Pure and Applied Geophysics, 2022)

Nucleases are upregulated in potato tubers afflicted with zebra chip disease - G. N. Mohan Kumar; C. G. Kannangara; N. Richard Knowles (Planta, 2022)

Impact of water deficit stress on traits influencing the drought tolerance and yield of maize (Zea mays L.) genotypes - P. Sathish; M. Vanaja; N. Jyothi Lakshmi; B. Sarkar; G. Vijay Kumar; P. Vagheera; C. H. Mohan; M. Maheswari (Plant Physiology Reports, 2022)

Occurrence of the supposedly endemic Australian azooxanthellate coral Astrangia woodsi Wells, 1955 in the eastern Arabian Sea - Divya Viswambharan; K. R. Sreenath; S. Jasmine; K. K. Joshi; C. R. Sreeraj; Smruthu Mohan; Prathibha Rohit (Marine Biodiversity, 2021)

Biomass and vegetation carbon stock in mangrove forests of the Andaman Islands, India - P. Ragavan; Sanjeev Kumar; K. Kathiresan; P. M. Mohan; R. S. C. Jayaraj; K. Ravichandaran; T. S. Rana (Hydrobiologia, 2021)

Ensuring the adaptive potential of Coastal wetlands of India- the need of the hour for sustainable management - P. Ragavan; K. Kathiresan; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; T. S. Rana (Wetlands Ecology and Management, 2021)

Ontogenetic Patterns of Elemental Tracers in the Vertebrae Cartilage of Coastal and Oceanic Sharks - Mariah C. Livernois; John A. Mohan; Thomas C. TinHan; Travis M. Richards; Brett J. Falterman; Nathan R. Miller; R. J. David Wells (Frontiers in Marine Science, 2021)
As predators, coastal and oceanic sharks play critical roles in shaping ecosystem structure and function, but most shark species are highly susceptible to population declines. Effective management of vulnerable shark populations requires knowledge of species-specific movement and habitat use patterns. Since sharks are often highly mobile and long-lived, tracking their habitat use patterns over large spatiotemporal scales is challenging. However, the analysis of elemental tracers in vertebral cartilage can describe a continuous record of the life history of an individual from birth to death. This study examined trace elements (Li, Mg, Mn, Zn, Sr, and Ba) along vertebral transects of five shark species with unique life histories. From most freshwater-associated to most oceanic, these species include Bull Sharks ( Carcharhinus leucas ), Bonnethead Sharks ( Sphyrna tiburo ), Blacktip Sharks ( Carcharhinus limbatus ), Spinner Sharks ( Carcharhinus brevipinna ), and Shortfin Mako Sharks ( Isurus oxyrinchus ). Element concentrations were compared across life stages (young-of-the-year, early juvenile, late juvenile, and adult) to infer species-specific ontogenetic patterns of habitat use and movement. Many of the observed elemental patterns could be explained by known life history traits: C. leucas exhibited clear ontogenetic changes in elemental composition matching expected changes in their use of freshwater habitats over time. S. tiburo elemental composition did not differ across ontogeny, suggesting residence in estuarine/coastal regions. The patterns of elemental composition were strikingly similar between C. brevipinna and C. limbatus , suggesting they co-occur in similar habitats across ontogeny. I. oxyrinchus elemental composition was stable over time, but some ontogenetic shifts occurred that may be due to changes in migration patterns with maturation. The results presented in this study enhance our understanding of the habitat use and movement patterns of coastal and oceanic sharks, and highlights the applicability of vertebral chemistry as a tool for characterizing shark life history traits.

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Genome Guided Bioprospecting of Extremely Halophilic Haloferax sp. AS1 for CAZymes, Bioremediation and Study Metabolic Versatility - Milind Mohan Naik; Md. Imran; Diviya C. Vaigankar; Sajiya Yusuf Mujawar; Alisha D. Malik; Sanket K. Gaonkar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

A novel transcript variant of human G-protein coupled estrogen receptor - Uttariya Pal; Mohan C. Manjegowda; Anil Mukund Limaye (Molecular Biology Reports, 2021)

Evaluation of Potentiality of Different Adjuvants for Date Palm Pollination and Fruit Set - Kapil Mohan Sharma; C. M. Muralidharan; D. A. Baidiyavadra; Kirti Bardhan; C. N. Panchal (Sugar Tech, 2021)

Thymosin β4 dynamics during chicken enteroid development - Mohan Acharya; Rohana Liyanage; Anamika Gupta; Komala Arsi; Ann M. Donoghue; Jackson O. Lay; Narayan C. Rath (Molecular and Cellular Biochemistry, 2021)
The sheared avian intestinal villus-crypts exhibit high tendency to self-repair and develop enteroids in culture. Presuming that this transition process involves differential biomolecular changes, we employed matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF–MS) to find whether there were differences in the spectral profiles of sheared villi versus the enteroids, assessed in the mass range of 2–18 kDa. The results showed substantial differences in the intensities of the spectral peaks, one particularly corresponding to the mass of 4963 Da, which was significantly low in the sheared villus-crypts compared with the enteroids. Based on our previous results with other avian tissues and further molecular characterization by LC-ESI-IT-TOF–MS, and multiple reaction monitoring (MRM), the peak was identified to be thymosin β4 (Tβ4), a ubiquitously occurring regulatory peptide implicated in wound healing process. The identity of the peptide was further confirmed by immunohistochemistry which showed it to be present in a very low levels in the sheared villi but replete in the enteroids. Since Tβ4 sequesters G-actin preventing its polymerization to F-actin, we compared the changes in F-actin by its immunohistochemical localization that showed no significant differences between the sheared villi and enteroids. We propose that depletion of Tβ4 likely precedes villous reparation process. The possible mechanism for the differences in Tβ4 profile in relation to the healing of the villus-crypts to developing enteroids is discussed.

Modeling Crude Oil Fate and Transport in Freshwater - Lillian C. Jeznach; Aarthi Mohan; John E. Tobiason; David A. Reckhow (Environmental Modeling & Assessment, 2021)

Breeding potential of crosses derived from parents differing in fruiting habit traits in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh (Genetic Resources and Crop Evolution, 2021)

Pistillate Receptivity of Date Palm (Phoenix dactylifera L.) cv. Barhee - C. M. Muralidharan; C. N. Panchal; D. A. Baidiyavadra; Kapil Mohan Sharma; Piyush Verma (Sugar Tech, 2020)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Vertical distributions of the microscopic morphological characteristics and elemental composition of aerosols over India - Mukunda M. Gogoi; Roseline C. Thakur; Sahina Gazi; Vijayakumar S. Nair; Rahul Mohan; S. Suresh Babu (Journal of Atmospheric Chemistry, 2020)

Impact of Boundary Layer Physics on Tropical Cyclone Simulations in the Bay of Bengal Using the WRF Model - J. R. Rajeswari; C. V. Srinivas; P. Reshmi Mohan; B. Venkatraman (Pure and Applied Geophysics, 2020)

Perchlorate contamination of drinking water sources in Kerala, South India, and its degradation using advanced chemical treatment - M. R. Sijimol; C. T. Aravindakumar; P. R. Manoj; D. Dineep; K. K. Nejumal; Mahesh Mohan (Energy, Ecology and Environment, 2020)

A review of inclusive business models and their application in aquaculture development - Alexander M. Kaminski; Froukje Kruijssen; Steven M. Cole; Malcolm C.M. Beveridge; Claire Dawson; Chadag V. Mohan; Sharon Suri; Manjurul Karim; Oai Li Chen; Michael J. Phillips; William Downing; Fred Weirowski; et al. (Reviews in Aquaculture, 2020)
For aquaculture to continue along its current growth trajectory and contribute towards achieving the Sustainable Development Goals, value chains must become more inclusive. Smallholders and other local value chain actors are often constrained by circumstances and market failures in the global aquaculture industry. Integrating these actors into aquaculture value chains through inclusive business models (IBMs) is often touted as a solution to sustainable and ethical trade and business that can generate development outcomes. We reviewed 36 papers under seven business models commonly used in agriculture development to assess their application in aquaculture value chains in lower‐income countries. A global value chain (GVC) analysis is used to unpack the economic and social upgrading objectives of the different IBMs, as well as the types of relational coordination used between actors in the chain to achieve development outcomes. The extent to which these IBMs helped poor actors overcome certain barriers is evaluated with a focus on how they may ensure or be a risk to inclusiveness through the relations and upgrading opportunities evident in their make‐up. The analysis found that the majority of the models focused on economic upgrading over social upgrading. Providing opportunities for the latter is key to achieving the inclusive objectives of IBMs. Greater horizontal coordination between actors can create further opportunities for economic upgrading established under vertical coordination with other nodes upstream and downstream in a value chain. There is a need to further contextualize these models to aquaculture systems and develop clear indicators of inclusiveness.

Industrial heat island: a case study of Angul-Talcher region in India - Manju Mohan; Vivek Kumar Singh; Shweta Bhati; Neelesh Lodhi; Ankur Prabhat Sati; Nihar Ranjan Sahoo; Simanchala Dash; P. C. Mishra; Sagnik Dey (Theoretical and Applied Climatology, 2020)

Rare Earth Elements in Andaman Island Surface Seawater: Geochemical Tracers for the Monsoon? - Ed C. Hathorne; Martin Frank; P. M. Mohan (Frontiers in Marine Science, 2020)

Untargeted metabolomics reveals alterations in metabolites of lipid metabolism and immune pathways in the serum of rats after long-term oral administration of Amalaki rasayana - Vikas Kumar; A. Aneesh Kumar; Vinod Joseph; Vipin Mohan Dan; Abdul Jaleel; T. R. Santhosh Kumar; Chandrasekharan C. Kartha (Molecular and Cellular Biochemistry, 2020)

Application of Marine Bacteria Associated with Seaweed, Ulva lactuca, for Degradation of Algal Waste - Milind Mohan Naik; Diksha Naik; Lakshangy Charya; Sajiya Y. Mujawar; Diviya C. Vaingankar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Regression-Based Integrated Bi-sensor SAR Data Model to Estimate Forest Carbon Stock - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. Santra Mitra; C. Jeganathan (Journal of the Indian Society of Remote Sensing, 2019)

Genetics of fruit yield and its component traits under different fruiting habit backgrounds in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh; B. Bhavani; Pranesh (Journal of Genetics, 2019)

Modelling Betula utilis distribution in response to climate-warming scenarios in Hindu-Kush Himalaya using random forest - Jakesh Mohapatra; Chandra Prakash Singh; Maroof Hamid; Anirudh Verma; Sudeep Chandra Semwal; Bandan Gajmer; Anzar A. Khuroo; Amit Kumar; Mohan C. Nautiyal; Narpati Sharma; Himanshu A. Pandya (Biodiversity and Conservation, 2019)

Probabilistic Seismic Hazard Assessment of Mangalore and Its Adjoining Regions, A Part of Indian Peninsular: An Intraplate Region - C. Shreyasvi; Katta Venkataramana; Sumer Chopra; Madan Mohan Rout (Pure and Applied Geophysics, 2019)

Plant Growth Enhancement, Disease Resistance, and Elemental Modulatory Effects of Plant Probiotic Endophytic Bacillus sp. Fcl1 - Aswathy Jayakumar; Arathy Krishna; Mahesh Mohan; Indu C. Nair; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Accounting tropical forest carbon stock with synergistic use of space-borne ALOS PALSAR and COSMO-Skymed SAR sensors - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. S. Mitra; C. Jeganathan (Tropical Ecology, 2019)

Presence of the Wondrous Jewel Squid Histioteuthis miranda (Cephalopoda: Histioteuthidae) in the Eastern Arabian Sea and Determination of its Age from Statoliths - K. K. Sajikumar; V. Venkatesan; C. P. Binesh; Gishnu Mohan; N. K. Sanil; V. Kripa; K. S. Mohamed (Thalassas: An International Journal of Marine Sciences, 2018)

Movement, Behavior, and Habitat Use of a Marine Apex Predator, the Scalloped Hammerhead - R. J. David Wells; Thomas C. TinHan; Michael A. Dance; J. Marcus Drymon; Brett Falterman; Matthew J. Ajemian; Gregory W. Stunz; John A. Mohan; Eric R. Hoffmayer; William B. Driggers; Jennifer A. McKinney (Frontiers in Marine Science, 2018)

Frequency of Heterotic Hybrids in Relation to Parental Genetic Divergence and General Combining Ability in Dolichos Bean - C. M. Keerthi; S. Ramesh; M. Byregowda; A. Mohan Rao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Linking Habitat Use and Trophic Ecology of Spotted Seatrout (Cynoscion nebulosus) on a Restored Oyster Reef in a Subtropical Estuary - Thomas C. TinHan; John A. Mohan; Mark Dumesnil; Bryan M. DeAngelis; R. J. David Wells (Estuaries and Coasts, 2018)

Mangrove floristics of the Andaman and Nicobar Islands: critical review and current scenario - P. Ragavan; P. M. Mohan; Alok Saxena; R. S. C. Jayaraj; K. Ravichandran; Mani Saxena (Marine Biodiversity, 2018)

Inhibition of proinflammatory pathways by bioactive fraction of Tinospora cordifolia - Jenny Jacob; Bashi M. Babu; Mohind C. Mohan; A. P. Abhimannue; B. Prakash Kumar (Inflammopharmacology, 2018)

Direct and indirect influences of intercrops on the coconut defoliator Opisina arenosella - K. S. Shameer; M. Nasser; Chandrika Mohan; Ian C. W. Hardy (Journal of Pest Science, 2018)

Presence of bisphenol S and surfactants in the sediments of Kongsfjorden: a negative impact of human activities in Arctic? - K. K. Nejumal; D. Dineep; Mahesh Mohan; K. P. Krishnan; U. K. Aravind; C. T. Aravindakumar (Environmental Monitoring and Assessment, 2018)

Detection of Tilapia Lake Virus in Egyptian fish farms experiencing high mortalities in 2015 - P Nicholson; M A Fathi; A Fischer; C Mohan; E Schieck; N Mishra; A Heinimann; J Frey; B Wieland; J Jores (Journal of Fish Diseases, 2017)

Effect of Vacuum Packaging and Sous Vide Processing on the Quality of Indian White Shrimp ( Fenneropenaeus indicus) During Chilled Storage - C. O. Mohan; C. N. Ravishankar; T. K. Srinivasa Gopal (Journal of Aquatic Food Product Technology, 2017)

Rescue of a recombinant Newcastle disease virus strain R2B expressing green fluorescent protein - Madhan Mohan Chellappa; Sohini Dey; Satish Gaikwad; Dinesh C. Pathak; Vikram N. Vakharia (Virus Genes, 2017)

Serum Lipid Alterations in Early Rheumatoid Arthritis Patients on Disease Modifying Anti Rheumatoid Therapy - Sana Parveen; Rachel Jacob; Liza Rajasekhar; C. Srinivasa; Iyyapu Krishna Mohan (Indian Journal of Clinical Biochemistry, 2017)

High-fructose diet is as detrimental as high-fat diet in the induction of insulin resistance and diabetes mediated by hepatic/pancreatic endoplasmic reticulum (ER) stress - M. Balakumar; L. Raji; D. Prabhu; C. Sathishkumar; P. Prabu; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2016)

Integration of common feature pharmacophore modeling and in vitro study to identify potent AChE inhibitors - Sneha Patil; Ankit Tyagi; Jane Jose.; Krishnakumar N. Menon; C. Gopi Mohan (Medicinal Chemistry Research, 2016)

MicroRNA in aquaculture fishes: a way forward with high-throughput sequencing and a computational approach - Kiran Dashrath Rasal; Priyanka C. Nandanpawar; Pranati Swain; Mohan R. Badhe; Jitendra Kumar Sundaray; Pallipuram Jayasankar (Reviews in Fish Biology and Fisheries, 2016)

Developing synergy regression models with space-borne ALOS PALSAR and Landsat TM sensors for retrieving tropical forest biomass - Suman Sinha; C Jeganathan; L K Sharma; M S Nathawat; Anup K Das; Shiv Mohan (Journal of Earth System Science, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Further evidence for the genetic basis of qualitative traits and their linkage relationships in dolichos bean (Lablab purpureus L.) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2016)

Summer monsoon onset-induced changes of autotrophic pico- and nanoplankton in the largest monsoonal estuary along the west coast of India - Arya P. Mohan; R. Jyothibabu; L. Jagadeesan; K. R. Lallu; C. Karnan (Environmental Monitoring and Assessment, 2016)

Interactions between nymphs of Nilaparvata lugens and Sogatella furcifera (Hemiptera: Delphacidae) on resistant and susceptible rice varieties - Thanga Suja Srinivasan; Maria Liberty P. Almazan; Carmencita C. Bernal; Angelee Fame Ramal; Mohan Kumar Subbarayalu; Finbarr G. Horgan (Applied Entomology and Zoology, 2016)

Mapping QTL for bruchid resistance in rice bean (Vigna umbellata) - Pavithravani B. Venkataramana; Rame Gowda; Prakit Somta; S. Ramesh; A. Mohan Rao; K. Bhanuprakash; Peerasak Srinives; C. Gireesh; C. K. Pramila (Euphytica, 2016)

Distribution and fractionation of mercury in the soils of a unique tropical agricultural wetland ecosystem, southwest coast of India - C Navya; VG Gopikrishna; V Arunbabu; Mahesh Mohan (Environmental Monitoring and Assessment, 2015)

Current utility of the BPH25 and BPH26 genes and possibilities for further resistance against plant- and leafhoppers from the donor cultivar ADR52 - Thanga Suja Srinivasan; Maria Liberty P. Almazan; Carmencita C. Bernal; Daisuke Fujita; Angelee Fame Ramal; Hidesi Yasui; Mohan Kumar Subbarayalu; Finbarr G. Horgan (Applied Entomology and Zoology, 2015)

Molecular Landscape of Helopeltis theivora Induced Transcriptome and Defense Gene Expression in Tea - Tirthankar Bandyopadhyay; Bornali Gohain; Raju Bharalee; Sushmita Gupta; Priyadarshini Bhorali; Sourabh Kumar Das; Mohan C. Kalita; Sudripta Das (Plant Molecular Biology Reporter, 2015)

Diversity, distribution and vegetative structure of mangroves of the Andaman and Nicobar Islands, India - P. Ragavan; Alok Saxena; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; S. Saravanan (Journal of Coastal Conservation, 2015)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Real-time numerical simulation of tropical cyclone Nilam with WRF: experiments with different initial conditions, 3D-Var and Ocean Mixed Layer Model - Greeshma M. Mohan; C. V. Srinivas; C. V. Naidu; R. Baskaran; B. Venkatraman (Natural Hazards, 2015)

Human Exposure Risks for Metals in Soil Near a Coal-Fired Power-Generating Plant - Joshy George; Reginald E. Masto; Lal C. Ram; Tarit B. Das; Tofan K. Rout; Mahesh Mohan (Archives of Environmental Contamination and Toxicology, 2015)

Histopathological findings on innate responses of white spot disease positive Penaeus monodon (Fabricius) under semi‐intensive culture - A K Sahoo; P C Thakur; K M Shankar; C V Mohan; S R Krupesha Sharma; F Corsin (Journal of Fish Diseases, 2015)

Why do satellite imageries show exceptionally high chlorophyll in the Gulf of Mannar and the Palk Bay during the Norteast Monsoon? - R. Jyothibabu; N. V. Madhu; L. Jagadeesan; A. Anjusha; Arya P. Mohan; N. Ullas; K. Sudheesh; C. Karnan (Environmental Monitoring and Assessment, 2014)

Purification and kinetic characterization of polygalacturonase - 3 from palmyrah palm (Borassus flabellifer L) - B. S. Sandeep; T. C. Kishor Mohan; K. Murugan (Journal of Plant Biochemistry and Biotechnology, 2014)

Genetics of growth habit and photoperiodic response to flowering time in dolichos bean (Lablab purpureus (L.) Sweet) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2014)

Increased circulatory levels of lipopolysaccharide (LPS) and zonulin signify novel biomarkers of proinflammation in patients with type 2 diabetes - B. Jayashree; Y. S. Bibin; D. Prabhu; C. S. Shanthirani; K. Gokulakrishnan; B. S. Lakshmi; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2014)

Structure–function prediction of α2A-, α2B-, and α2C-adrenoceptors using homology model assisted antagonist binding study - Vivek Kumar; Gourja Bansal; Jignesh Patel; C. Gopi Mohan (Medicinal Chemistry Research, 2014)

Uridine monophosphate kinase as potential target for tuberculosis: From target to lead identification - Akanksha Arvind; Vaibhav Jain; Parameswaran Saravanan; C. Gopi Mohan (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Deep transcriptome sequencing reveals the expression of key functional and regulatory genes involved in the abiotic stress signaling pathways in rice - R. C. Venu; M. V. Sreerekha; M. Sheshu Madhav; Kan Nobuta; K. Madhan Mohan; Songbiao Chen; Yulin Jia; Blake C. Meyers; Guo-Liang Wang (Journal of Plant Biology, 2013)

Anticonvulsant activity of 1,2,3,4,6-penta-O-galloyl-β-d-glucopyranose isolated from leaves of Mangifera indica - G. L. Viswanatha; C. G. Mohan; H. Shylaja; H. C. Yuvaraj; V. Sunil (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Multiple Approaches Towards Decolorization and Reuse of a Textile Dye (VB-B) by a Marine Bacterium Shewanella decolorationis - S. Satheesh Babu; C. Mohandass; A. S. Vijay Raj; R. Rajasabapathy; Mohan A. Dhale (Water, Air, & Soil Pollution, 2013)

Provenance and temporal variability of ice rafted debris in the Indian sector of the Southern Ocean during the last 22,000 years - M C MANOJ; MELOTH THAMBAN; A SAHANA; RAHUL MOHAN; KOTHA MAHENDER (Journal of Earth System Science, 2013)

Homology modeling, molecular dynamics and inhibitor binding study on MurD ligase of Mycobacterium tuberculosis - Akanksha Arvind; Vivek Kumar; Parameswaran Saravanan; C. Gopi Mohan (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Design, synthesis, and biological evaluation of novel 2,4-thiazolidinedione derivatives as histone deacetylase inhibitors targeting liver cancer cell line - Rhea Mohan; Ajit K. Sharma; Sanjay Gupta; C. S. Ramaa (Medicinal Chemistry Research, 2012)

Evidence for climatic and oceanographic controls on terrigenous sediment supply to the Indian Ocean sector of the Southern Ocean over the past 63,000 years - Madhusudhanan C. Manoj; Meloth Thamban; Natani Basavaiah; Rahul Mohan (Geo-Marine Letters, 2012)

Synthesis and preliminary evaluation of difluorinated 1,3-propanediones as potential agents in the treatment of breast cancer - Tabreskhan Pathan; Sachin Ingale; Ashish Sharma; Rhea Mohan; C. S. Ramaa (Medicinal Chemistry Research, 2012)

Bio-conventional bleaching of kadam kraft-AQ pulp by thermo-alkali-tolerant xylanases from two strains of Coprinellus disseminatus for extenuating adsorbable organic halides and improving strength with optical properties and energy conservation - Mohan Lal; Dharm Dutt; C. H. Tyagi (World Journal of Microbiology and Biotechnology, 2012)

Expression of medium and heavy chain neurofilaments in the developing human auditory cortex - Arvind Singh Pundir; L. Shahul Hameed; P. C. Dikshit; Praveen Kumar; Surender Mohan; Bishan Radotra; S. K. Shankar; Anita Mahadevan; Soumya Iyengar (Brain Structure and Function, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Composition and antibacterial activity of essential oil from Scutellaria grossa Wall ex Benth. - Charu C. Pant; Anand B. Melkani; Lalit Mohan; Vasu Dev (Natural Product Research, 2012)

3D-pharmacophore model based virtual screening to identify dual-binding site and selective acetylcholinesterase inhibitors - Shikhar Gupta; C. Gopi Mohan (Medicinal Chemistry Research, 2011)

The Role of IL-1β in Nicotine-Induced Immunosuppression and Neuroimmune Communication - Seddigheh Razani-Boroujerdi; Raymond J. Langley; Shashi P. Singh; Juan Carlos Pena-Philippides; Jules Rir-sima-ah; Sravanthi Gundavarapu; Neerad C. Mishra; Mohan L. Sopori (Journal of Neuroimmune Pharmacology, 2011)

Q2N and S65D Substitutions of Ubiquitin Unravel Functional Significance of the Invariant Residues Gln2 and Ser65 - Pradeep Mishra; C. Ratna Prabha; Ch. Mohan Rao; Srinivas Volety (Cell Biochemistry and Biophysics, 2011)

Evaluation of wood extract of Dysoxylum malabaricum Bedd. against the plant pathogenic fungus, Fusarium oxysporum Schlecht - S. Mohan; H. C. Nagaveni; S. H. Jain; G. Ravikumar (Journal of the Indian Academy of Wood Science, 2011)

Impaired miR-146a expression links subclinical inflammation and insulin resistance in Type 2 diabetes - M. Balasubramanyam; S. Aravind; K. Gokulakrishnan; P. Prabu; C. Sathishkumar; H. Ranjani; V. Mohan (Molecular and Cellular Biochemistry, 2011)

Age-induced loss of wound-healing ability in potato tubers is partly regulated by ABA - G. N. Mohan Kumar; Edward C. Lulai; Jeffrey C. Suttle; N. Richard Knowles (Planta, 2010)

Leaf-eating caterpillar ( Opisina arenosella)-induced yield loss in coconut palm - Chandrika Mohan; C.P. Radhakrishnan Nair; C. Kesavan Nampoothiri; P. Rajan (International Journal of Tropical Insect Science, 2010)

Land-cover change dynamics and coastal aquaculture development: a case study in the East Godavari delta, Andhra Pradesh, India using multi-temporal satellite data - K. Rajitha; C. K. Mukherjee; R. Vinu Chandran; M. M. Prakash Mohan (International Journal of Remote Sensing, 2010)

Clinical white spot disease status in Penaeus monodon during the middle of the culture period – its epidemiological significance - A K Sahoo; C V Mohan; K M Shankar; F Corsin; J F Turnbull; P C Thakur; N V Hao; K L Morgan; A P Padiyar (Journal of Fish Diseases, 2010)

Comparative molecular field analysis and comparative molecular similarity indices analysis of hydroxyethylamine derivatives as selective human BACE-1 inhibitor - Ashish Pandey; Jignesh Mungalpara; C. Gopi Mohan (Molecular Diversity, 2010)

EfeO-cupredoxins: major new members of the cupredoxin superfamily with roles in bacterial iron transport - Mohan B. Rajasekaran; Sanjay Nilapwar; Simon C. Andrews; Kimberly A. Watson (BioMetals, 2010)

Management of Multipurpose Multireservoir Using Fuzzy Interactive Method - K. Deep; Krishna Pratap Singh; M. L. Kansal; C. Mohan (Water Resources Management, 2009)

Auxin-binding proteins without KDEL sequence in the moss Funaria hygrometrica - Kishore C. S. Panigrahi; Madhusmita Panigrahy; Marco Vervliet-Scheebaum; Daniel Lang; Ralf Reski; Man Mohan Johri (Plant Cell Reports, 2009)

Molecular mapping of rice blast resistance gene Pi-1(t) in the elite indica variety Samba mahsuri - M. Srinivas Prasad; B. Aruna Kanthi; S. M. Balachandran; M. Seshumadhav; K. Madhan Mohan; B. C. Viraktamath (World Journal of Microbiology and Biotechnology, 2009)

Assessment of large-scale deforestation of Nawarangpur district, Orissa, India: a remote sensing based study - C. Sudhakar Reddy; K. Ram Mohan Rao; Chiranjibi Pattanaik; P. K. Joshi (Environmental Monitoring and Assessment, 2009)

Isolation, identification and testing for allergenicity of fungi from air-conditioned indoor environments - A. A. Haleem Khan; S. Mohan Karuppayil; C. Manoharachary; I. K. Kunwar; S. Waghray (Aerobiologia, 2009)

Viral disease emergence in shrimp aquaculture: origins, impact and the effectiveness of health management strategies - Peter J. Walker; C. V. Mohan (Reviews in Aquaculture, 2009)
Shrimp aquaculture has grown rapidly over several decades to become a major global industry that serves the increasing consumer demand for seafood and has contributed significantly to socio‐economic development in many poor coastal communities. However, the ecological disturbances and changes in patterns of trade associated with the development of shrimp farming have presented many of the pre‐conditions for the emergence and spread of disease. Shrimp are displaced from their natural environments, provided artificial or alternative feeds, stocked in high density, exposed to stress through changes in water quality and are transported nationally and internationally, either live or as frozen product. These practices have provided opportunities for increased pathogenicity of existing infections, exposure to new pathogens, and the rapid transmission and transboundary spread of disease. Not surprisingly, a succession of new viral diseases has devastated the production and livelihoods of farmers and their sustaining communities. This review examines the major viral pathogens of farmed shrimp, the likely reasons for their emergence and spread, and the consequences for the structure and operation of the shrimp farming industry. In addition, this review discusses the health management strategies that have been introduced to combat the major pathogens and the reasons that disease continues to have an impact, particularly on poor, small‐holder farmers in Asia.

Burnt area mapping of Bandipur National Park, India using IRS 1C/1D LISS III data - R. K. Somashekar; P. Ravikumar; C. N. Mohan Kumar; K. L. Prakash; B. C. Nagaraja (Journal of the Indian Society of Remote Sensing, 2009)

Origin and characterisation of microparticles in an ice core from the Central Dronning Maud Land, East Antarctica - C. M. Laluraj; K. P. Krishnan; M. Thamban; R. Mohan; S. S. Naik; W. D’Souza; R. Ravindra; A. Chaturvedi (Environmental Monitoring and Assessment, 2009)

Evaluation of rice–legume–rice cropping system on grain yield, nutrient uptake, nitrogen fixation, and chemical, physical, and biological properties of soil - Dwipendra Thakuria; Narayan C. Talukdar; Chandan Goswami; Samarendra Hazarika; Mohan C. Kalita; Gary D. Bending (Biology and Fertility of Soils, 2009)

β-Funaltrexamine Inhibits Inducible Nitric-oxide Synthase Expression in Human Astroglial Cells - Randall L. Davis; Daniel J. Buck; Neda Saffarian; Shekher Mohan; Udaya DeSilva; Samodha C. Fernando; Craig W. Stevens (Journal of Neuroimmune Pharmacology, 2008)

Development of formaldehyde-free leathers in the perspective of retanning: part II. Combination of formaldehyde-free retanning syntans - C. Ram Mohan; S. Saravanabhavan; P. Thanikaivelan; J. Raghava Rao; Balachandran Unni Nair (Clean Technologies and Environmental Policy, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Hormone receptor-related gene polymorphisms and prostate cancer risk in North Indian population - Khadijeh Onsory; R. C. Sobti; Adnan Issa Al-Badran; Masatoshi Watanabe; Taizo Shiraishi; Awtar Krishan; Harsh Mohan; Pushpinder Kaur (Molecular and Cellular Biochemistry, 2008)

Genetic Diversity Analysis of Starchy Curcuma Species Using RAPD Markers - G. R. Angel; T. Makeshkumar; C. Mohan; B. Vimala; B. Nambisan (Journal of Plant Biochemistry and Biotechnology, 2008)

Strain improvement of Aspergillus niger for the enhanced production of asperenone - C. Chidananda; C. Mohan Kumar; A. P. Sattur (Indian Journal of Microbiology, 2008)

Synergistic interaction between sublethal doses of Bacillus thuringiensis and Campoletis chlorideae in managing Helicoverpa armigera - M. Mohan; S. N. Sushil; J. C. Bhatt; G. T. Gujar; H. S. Gupta (BioControl, 2008)

ATRA promotes alpha tocopherol succinate-induced apoptosis in freshly isolated leukemic cells from chronic myeloid leukemic patients - Surender Kumar; Krishan Lal Khanduja; Neelam Verma; Subhash C. Verma; Pramod Kumar Avti; Chander Mohan Pathak (Molecular and Cellular Biochemistry, 2007)

A deterministic approach for preparation of seismic hazard maps in North East India - A. Joshi; Kapil Mohan; R. C. Patel (Natural Hazards, 2007)

Phylogenetic Analysis of LipL32 Gene Sequence of Different Pathogenic Serovars of Leptospira - Sohini Dey; C. Madhan Mohan; P. Ramadass; K. Nachimuthu (Veterinary Research Communications, 2007)

Purification and Characterization of Polygalacturonase-3 from Jamaica cherry (Muntingia calabura Linn) - T. Gayathri; T. C. Kishor Mohan; K. Murugan (Journal of Plant Biochemistry and Biotechnology, 2007)

Pattern and genesis of lineaments in and across son-Narmada lineament zone in a part of central India around Renukoot, district Sonbhadra, U.P. - Kshitij Mohan; Vaibhava Srivastava; C. K. Singh (Journal of the Indian Society of Remote Sensing, 2007)

Adaptation of a Velogenic Newcastle Disease Virus to Vero Cells: Assessing the Molecular Changes Before and After Adaptation - C. Madhan Mohan; Sohini Dey; K. Kumanan; B. Murali Manohar; A. Mahalinga Nainar (Veterinary Research Communications, 2007)

Recombinant Antigen-based Latex Agglutination Test for Rapid Serodiagnosis of Leptospirosis - S. Dey; C. Madhan Mohan; P. Ramadass; K. Nachimuthu (Veterinary Research Communications, 2007)

Sclerotiorin, from Penicillium frequentans, a potent inhibitor of aldose reductase - C. Chidananda; L. Jagan Mohan Rao; A. P. Sattur (Biotechnology Letters, 2006)

Restriction Enzyme Analysis of Tissue Culture-adapted Velogenic Newcastle Disease Virus - C. Madhan Mohan; Sohini Dey; K. Kumanan (Veterinary Research Communications, 2006)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Changes in the source and transport mechanism of terrigenous input to the Indian sector of Southern Ocean during the late Quaternary and its palaeoceanographic implications - M. Thamban; S. S. Naik; R. Mohan; A. Rajakumar; N. Basavaiah; Witty D’Souza; Sarita Kerkar; M. M. Subramaniam; M. Sudhakar; P. C. Pandey (Journal of Earth System Science, 2005)

Promoter Trapping in Arabidopsis Using T-DNA Insertional Mutagenesis - Radhamony Resminath; Anand Mohan Prasad; Dhiraj R. Thakare; C. Sivanandan; S. R. Bhat; Srinivasan (Journal of Plant Biochemistry and Biotechnology, 2005)

Standardisation of true cassava seed (TCS) programme with special emphasis on more homogeneous, CMD resistant progenies - P. G. Rajendran; C. Mohan; J. Sreekumar (Euphytica, 2005)

Use of sugarcane bagasse as an alternative low-cost support material during the rooting stage of apple micropropagation - R. Mohan; C. R. Soccol; M. Quoirin; A. Pandey (In Vitro Cellular & Developmental Biology - Plant, 2004)

Rubella virus P90 associates with the cytokinesis regulatory protein Citron-K kinase and the viral infection and constitutive expression of P90 protein both induce cell cycle arrest following S phase in cell culture - C. D. Atreya; S. Kulkarni; K.V. K. Mohan (Archives of Virology, 2004)

Stress and aberrant phenotypes in vitro culture - Siobhan M. Joyce; Alan C. Cassells; S. Mohan Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Effect of dietary vitamin C on the inflammatory response of mrigal, Cirrhinus mrigala (Hamilton), to Freund's complete adjuvant - K S Sobhana; C V Mohan; K M Shankar (Journal of Fish Diseases, 2002)

Cytoplasmic effects on photosynthesis and ribulose-1,5-bisphosphate carboxylase activity in Brassica species - Sivakoti Ramana; Poonam Sharma-Natu; Mohan C. Ghildiyal (Euphytica, 2002)

Simulating the influence of two shallow, flow-through lakes on a groundwater system: implications for groundwater mounds and hinge lines - David C. Gosselin; Mohan J. Khisty (Hydrogeology Journal, 2001)

Hydrogeologic framework of the Deccan terrain of the Koyna River basin, India - Pradeep K. Naik; Arun K. Awasthi; A. Anand; Prakash C. Mohan (Hydrogeology Journal, 2001)

Comparative sequence analysis identified mutations outside the NSP4 cytotoxic domain of tissue culture-adapted ATCC-Wa strain of human rotavirus and a novel inter-species variable domain in its C-terminus - K. V. Krishna Mohan; C. D. Atreya (Archives of Virology, 2000)

Occurrence of unusual giant cells in the heart of Penaeus monodon Fabricus, showing gross signs of yellow head syndrome - C V. Mohan (Journal of Fish Diseases, 1999)

The complete primary structure of mouse 20S proteasomes - Laura A. Elenich; D. Nandi; A. Elizabeth Kent; T. Scott McCluskey; M. Cruz; Mohan N. Iyer; Elaine C. Woodward; Christopher W. Conn; Amber L. Ochoa; David B. Ginsburg; J. J. Monaco (Immunogenetics, 1999)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genome analysis for nucleotide interactions in fully sequenced genomes of selective prokaryotes - B. V. L. S. Prasaot; Mohan C. Vemuri (Journal of Biosciences, 1998)

Development and Field Performance of a Sporeless Mutant of Bacillus thuringiensis Subsp. kurstaki - K. S. Mohan; R. Asokan; C. Gopalakrishnan (Journal of Plant Biochemistry and Biotechnology, 1997)

Regulation of cellular signals by G-proteins - K. Sandhya; Mohan C. Vemuri (Journal of Biosciences, 1997)